3(t-4)=5(t+1)-1

Simple and best practice solution for 3(t-4)=5(t+1)-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(t-4)=5(t+1)-1 equation:


Simplifying
3(t + -4) = 5(t + 1) + -1

Reorder the terms:
3(-4 + t) = 5(t + 1) + -1
(-4 * 3 + t * 3) = 5(t + 1) + -1
(-12 + 3t) = 5(t + 1) + -1

Reorder the terms:
-12 + 3t = 5(1 + t) + -1
-12 + 3t = (1 * 5 + t * 5) + -1
-12 + 3t = (5 + 5t) + -1

Reorder the terms:
-12 + 3t = 5 + -1 + 5t

Combine like terms: 5 + -1 = 4
-12 + 3t = 4 + 5t

Solving
-12 + 3t = 4 + 5t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-5t' to each side of the equation.
-12 + 3t + -5t = 4 + 5t + -5t

Combine like terms: 3t + -5t = -2t
-12 + -2t = 4 + 5t + -5t

Combine like terms: 5t + -5t = 0
-12 + -2t = 4 + 0
-12 + -2t = 4

Add '12' to each side of the equation.
-12 + 12 + -2t = 4 + 12

Combine like terms: -12 + 12 = 0
0 + -2t = 4 + 12
-2t = 4 + 12

Combine like terms: 4 + 12 = 16
-2t = 16

Divide each side by '-2'.
t = -8

Simplifying
t = -8

See similar equations:

| 2x=4(x+3) | | -12x=-120 | | 45x^2+20x=45x+20 | | -16=-25-x | | 6p+p=7p | | -5/8w+2/5=-7/8w+1/8 | | 5x^2+x-328=0 | | -7=-10+x | | X^2+11x+35=5 | | 8P^4*3p= | | 25x-5+10x= | | 2x^4-4x^3-3=0 | | 3-2/2+6=z+8 | | X^2+42X-43=0 | | 7-3x=x-4(2+6) | | b+3=33-b | | 3-9=4x+4 | | x=250+0.8(x-(325+0.25x))+650-80i+560 | | 1x^2-30x=0 | | 6x^2-5x=x | | 4x-12=24+8x | | 11x+12y=150 | | (x^2+7x-48)/(x+9) | | 6x-3(x-4)=2(x+7)+x | | p^2-13p+36=0 | | 4x+16=-12 | | 10-2x=9-5x | | 4(3x-5)=4x+4 | | -3p^3+3p^2+6p=0 | | -2x-14=4(x-2) | | 5(x+2)=-40 | | 3m+3=m-1 |

Equations solver categories